PENGARUH METODE GAME BASED LEARNING PADA MATA KULIAH AGAMA ISLAM TERHADAP INTERPERSONAL DAN INTRAPERSONAL SKILLS MAHASISWA - Muchamad Saiful Muluk; Ibnu Athaillah; Moch. Kholil (STAI Pelabuhan Ratu, 2025)
In welcoming the era of society 5.0, higher education through its tri dharma activities is required to produce graduates who are not only competent in sciences and technologies and their applications, but also have self-confidence in their knowledge and have the capacity for a good attitude. One step to making this happen is by studying personality development courses, such as Islamic religion courses. The focus of this research is to look at the effect of applying game-based learning methods on the interpersonal and intrapersonal skills of students at Putra Sang Fajar Blitar State Community College. The number of samples (n) is 48 from a population (N) of 120 students. Data was collected by questionnaire using Google Form and analyzed using SmartPLS version 3.0 with SEM (Stuctural Equation Modelling) analysis based on the output of the Iner Model and Outer Model. The research results show that there is a significant influence of game-based learning on interpersonal skills (path coefficient = 0.674) and intrapersonal skills (path coefficient = 0.746). This indicated that applying the game-based learning method in Islamic religion courses has a significant influence on interpersonal skills, as much as 67.4% and intrapersonal skills, as much as 74.6%, so the game-based learning method can be applied in personality development courses.